Volume 1: Materials; Micro and Nano Technologies; Properties, Applications and Systems; Sustainable Manufacturing 2014
DOI: 10.1115/msec2014-4194
|View full text |Cite
|
Sign up to set email alerts
|

Internet-of-Things-Enabled Smart Production Logistics Execution System Based on Cloud Manufacturing

Abstract: With the rapid development of cloud computer concept and technologies, more and more cloud-based business mode and practical applications are emerging in industrial environments, including cloud manufacturing and cloud logistics. Such cloud systems integrate the distributed resources and make best use of them to fulfill dynamic tasks in an optimal way. This paper will demonstrate a simple yet practical application of a cloud-based production logistics (PL) management system (C-PLES) developed under Internet-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Scheduling in cloud manufacturing is more complex and dynamic compared with preceding manufacturing models. The complexity of scheduling in cloud manufacturing comes from the involvement of wide-area logistics and the complexity of resources (Qu et al 2014). Manufacturing enterprises registered in a cloud manufacturing system are distributed in wide areas, which makes logistics indispensable for scheduling in cloud manufacturing Zhong et al 2016).…”
Section: 324mentioning
confidence: 99%
“…Scheduling in cloud manufacturing is more complex and dynamic compared with preceding manufacturing models. The complexity of scheduling in cloud manufacturing comes from the involvement of wide-area logistics and the complexity of resources (Qu et al 2014). Manufacturing enterprises registered in a cloud manufacturing system are distributed in wide areas, which makes logistics indispensable for scheduling in cloud manufacturing Zhong et al 2016).…”
Section: 324mentioning
confidence: 99%
“…Many smart manufacturing paradigms are proposed and the key technologies of which are further investigated as summarized in Table 1. Capturing real-time data of manufacturing resources and making better-informed enterprises decisions (Bi et al, 2014;Zhang et al, 2015); improving energy-aware production management (Shrouf and Miragliotta, 2015), smart production-logistics (Qu et al, 2014), supply chain management (Ben-Daya et al, 2019), production planning and scheduling (Tian et al, 2019; Cloud manufacturing IoT, cloud computing Providing on-demand capabilities of distributed manufacturing resources for meeting personalized manufacturing requirements (Tao et al, 2014;Xu, 2012;Zhang et al, 2017b) Edge and Fog-based IoT, edge and Enabling the application of business logic between manufacturing fog computing the downstream data of services and the upstream data of devices in the smart factory (Chen et al, 2018;Wu et al, 2017) Social manufacturing IoT, CPS…”
Section: Ict-driven Smart Manufacturing Paradigmsmentioning
confidence: 99%
“…The results showed that the system offers enhanced capabilities of monitoring and analyzing the production flow and also leads to decreased costs, defect parts and increased production efficiency through better workload balancing. An IoT approach to cloud-based production logistics planning is introduced by Qu et al (2014). The proposed approach was implemented in a paint factory which consisted of 19 palletizing points and two warehouses.…”
Section: Manufacturing Systems and Network Managementmentioning
confidence: 99%